2007
DOI: 10.1111/j.1475-2743.2007.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus losses at the catchment scale within Europe: an overview

Abstract: Quantifying P losses to surface waters at different scales and partitioning of the loads into P losses from point sources and diffuse sources are significant future challenges for river basin managers. The agricultural share of P losses to surface waters is, in many river basins, increasing and therefore becoming more important to quantify and analyse. The importance of phosphorus losses from agricultural land was analysed using monitoring data and two different models for 35 micro-catchments (<30 km 2 ) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 32 publications
7
65
2
Order By: Relevance
“…11 The TP export from the terrestrial biosphere to the river network at the 1 km 2 scale land use at a global scale (Moree et al 2013); global soils (Van Vuuren et al 2010) or the projection of global P demand (Bouwman et al 2009). Kronvang et al (2007) modelled the TP flux from European countries draining into the Danube and calculated fluxes between 0.07 and 0.12 tonnes P/km 2 . Seitzinger et al (2005) estimated that the global flux of TP to the oceans was 11 Mtonnes P/year (0.074 tonnes P/km 2 /year) compared to 9 Mtonnes P/year (Meybeck 1982) and 20 Mtonnes P/year (Mackenzie et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…11 The TP export from the terrestrial biosphere to the river network at the 1 km 2 scale land use at a global scale (Moree et al 2013); global soils (Van Vuuren et al 2010) or the projection of global P demand (Bouwman et al 2009). Kronvang et al (2007) modelled the TP flux from European countries draining into the Danube and calculated fluxes between 0.07 and 0.12 tonnes P/km 2 . Seitzinger et al (2005) estimated that the global flux of TP to the oceans was 11 Mtonnes P/year (0.074 tonnes P/km 2 /year) compared to 9 Mtonnes P/year (Meybeck 1982) and 20 Mtonnes P/year (Mackenzie et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It has subsequently been applied throughout Europe, e.g. to the Elbe, Rhine (De Wit and Behrendt, 1999;De Wit, 2000), Odra Behrendt and Dannowski, 2005), Danube (Schreiber et al, 2005), Po (Palmeri et al, 2005), Axios, Daugava, and Vistula rivers (Kronvang et al, 2007). For La Tordera, limited data availability advised against the use of a complex, dynamic model with higher temporal resolution.…”
Section: The Moneris Modelmentioning
confidence: 99%
“…Also no relationship could be developed between total phosphorus (TP) loss and P surplus on agricultural land in the 35 Nordic and Baltic investigated micro-catchments [KRONVANG et al 2007].…”
Section: Selected Problems Analyzed By River Eutrophication Studies Umentioning
confidence: 99%
“…A review of the professional literature in Poland of drainage waters has shown that analysed concentrations of 1 dm 3 most often do not exceed 20 mg N-NO 3 and 0.07 mg PO 4 [LIPIŃSKI 2000]. In an European review of micro-catchments, soil erosion and surface runoff was the dominant (53.4%) diffuse pathway [KRONVANG et al 2007]. Concentrations of phosphorus in drain water are very low (<0.1 mg P·l -1 ), in the main containing soluble inorganic P, which as a rule is lower than in the neighbouring stream and moreover, it is difficult to quantify the relationship between soil P concentrations measured in the topsoil and at the drain depth [DILS, HEATH-WAITE 1999].…”
Section: Tile Drainage Impact On Nutrient Leachingmentioning
confidence: 99%
See 1 more Smart Citation